FEATURES OF THE PRINT MEDIA FUNCTIONING IN PRYKARPATTYA REGION IN THE CONTEXT OF STATE-BUILDING - Марчук, Г. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article clarifies the peculiarities of coverage of the problem of state-building by the print media of the Prykarpattya region, and analyzes publications on state-building problems as one of the main thematic categories of the press of the oblast.